2015
DOI: 10.1111/jdv.13456
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease fibrosis score in patients with psoriasis

Abstract: Patients with psoriasis should be screened for common causes of liver disease, including NAFLD and liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 42 publications
5
43
1
1
Order By: Relevance
“…Initial case reports documented psoriasis in three patients with NASH, a patient with NASH and comorbid type 2 diabetes and psoriasis, and a patient with psoriasis, increased insulin resistance markers, elevated liver enzymes and NASH . Thereafter, investigations into a possible link between psoriasis and NAFLD ensued, and in each controlled retrospective or prospective study, the prevalence of NAFLD was significantly higher in patients with psoriasis than in healthy or matched controls (17–66% vs. 8–35%, respectively) . Additionally, patients with psoriasis were at significantly increased risk for NAFLD than controls (odds ratio 2·15) in a systematic review and meta‐analysis of seven case–controlled studies, six of which assessed risk of NAFLD among individuals with and without psoriasis …”
Section: The Evidence: a Link Between Psoriasis And Nonalcoholic Fattmentioning
confidence: 99%
See 3 more Smart Citations
“…Initial case reports documented psoriasis in three patients with NASH, a patient with NASH and comorbid type 2 diabetes and psoriasis, and a patient with psoriasis, increased insulin resistance markers, elevated liver enzymes and NASH . Thereafter, investigations into a possible link between psoriasis and NAFLD ensued, and in each controlled retrospective or prospective study, the prevalence of NAFLD was significantly higher in patients with psoriasis than in healthy or matched controls (17–66% vs. 8–35%, respectively) . Additionally, patients with psoriasis were at significantly increased risk for NAFLD than controls (odds ratio 2·15) in a systematic review and meta‐analysis of seven case–controlled studies, six of which assessed risk of NAFLD among individuals with and without psoriasis …”
Section: The Evidence: a Link Between Psoriasis And Nonalcoholic Fattmentioning
confidence: 99%
“…Although both psoriasis and NAFLD are associated with metabolic conditions, such as MetS, insulin resistance and obesity, it was unclear whether psoriasis could be independently associated with NAFLD. Recently, two studies demonstrated that psoriasis was a significant predictor of liver disease, and in elderly patients, psoriasis was independently associated with a 70% increased likelihood for developing NAFLD . When patients with and without psoriasis were compared, NAFLD Fibrosis Scores (−1·57 vs. −3·10; P ≤ 0·0001), presence of steatosis (44·3% vs. 34·0%; P = 0·02) and presence of advanced liver fibrosis (8·1% vs. 3·6%; P = 0·05) were significantly higher in patients with psoriasis; drug exposure was not evaluated .…”
Section: The Evidence: a Link Between Psoriasis And Nonalcoholic Fattmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence that NAFLD is a multisystemic disease, affecting extra‐hepatic organs, and it has been associated with different disorders such as cardiovascular diseases, T2DM, chronic kidney disease, several endocrinopathies, osteoporosis and psoriasis . In this sense, the association between NAFLD and psoriasis has been well established . However, despite HS and psoriasis share a chronic systemic inflammatory state, the association between HS and NAFLD has not been previously described.…”
Section: Introductionmentioning
confidence: 99%